EFFECTIVE TECHNIQUES FOR TEACHING BASIC GRAMMAR - Ibayev Anvar Jurabekovich,; Usarova Ruxshona Asqad qizi, (TADQIQOTLAR, 2026)
Abstract: One of the biggest problems in language education is still teaching basic grammar well, especially at the beginning of the learning process. Grammar is the structure that lets people speak and write clearly and meaningfully in a language they don’t know. But traditional grammar lessons often focus too much on memorizing rules and doing mechanical exercises, which can make students less interested and less able to use the language in real life. Because of this, modern teaching methods stress the  use  of  interactive,  communicative,  and  learner-centered  techniques  that  help students understand grammar in real-life situations. Teaching grammar well starts with showing  grammatical  forms  in  real-life  language  situations  instead  of  just  giving students rules. When students learn in context, they can see how grammar works in real-life situations. Teachers can teach grammar by using short conversations, stories, or real-life situations to show how certain structures are used. This method not only makes it easier for students to understand, but it also helps them remember forms better because they connect grammar to how language is actually used. Another good way to teach grammar is through inductive learning, where students figure out the rules by looking at examples instead of getting direct explanations first. Learners find patterns and connections between words in sentences through guided activities. This process helps people think critically and learn more about grammar.